Metadata Extraction Analysis: A Review of Video Data in Effect to Social Media Compression - Dawn Iris Calibo; Jasmin D. Niguidula (JOIV : International Journal on Informatics Visualization, 2019)
In the 21st century, the unending improvement of the web, online networking has made approaches to take advantage to streamline the speed of its webpage. Through metatadta extraction, two of the most well-known social networking sites were subjected to experimentation to see the impacts of video compression using standard parameters when uploaded to the said sites. The assessment demonstrates that both sites display keys similarities and differences. It is further explained in the research the different structures amongst the social network that create the outcome